Rare postpartum ruptured degenerated fibroid: A case report. Issue 5 (2nd April 2014) - Tan, Yiap L.; Naidu, Aruku
Abstract Spontaneous rupture of uterine fibroid is rarely encountered. We present a case of a 31‐year‐old who presented with acute abdominal pain at 9 weeks postpartum. On examination, the abdomen had diffuse tenderness, with rebound tenderness in the suprapubic area and in both iliac fossae. On ultrasonography, a 12.7 × 8.6 × 8.9‐cm sized hyperechoic mass was visible on the posterior wall of the uterus. A large amount of fluid was visible in the paracolic gutters and the Pouch of Douglas (POD). The patient underwent an exploratory laparotomy. A ruptured, cystic degenerated uterine fibroid with active bleeding was found, as well as approximately half a liter of free, bloodstained peritoneal fluid and pus. Myomectomy was performed, followed by evacuation of the fluid and clots. The patient's postoperative course was uneventful. In conclusion, preoperative diagnosis of a perforated, uterine fibroid with spontaneous intra‐abdominal hemorrhage is difficult; exploratory laparotomy is both diagnostic and therapeutic in this rare, life‐threatening condition.